Children's participation in LAC reviews: a study in one English local authority. (6th November 2014) - Pert, Hayley; Diaz, Clive; Thomas, Nigel
Abstract: Although the law in England and Wales requires a child's wishes and feelings to be heard in LAC (Looked After Children) reviews, there remains limited research into how far this is achieved. This study interviewed 25 children and 16 foster carers to explore how well children understand and take part in reviews, and what factors impede this. The study found that levels of participation, as experienced by children and foster carers, were very low and the methods used were relatively ineffective. Children experienced significant barriers in engaging with the review process. The paper concludes that, as a vehicle of children's participation, LAC reviews are still not working well and calls for more attention to the views of children and young people and to the effectiveness of LAC reviews.